2016
DOI: 10.1186/s12955-016-0430-x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the complementarity of ICECAP-A and EQ-5D-3 L in an adult population of patients with knee pain

Abstract: BackgroundThe ICECAP measures potentially offer a broader assessment of quality of life and well-being, in comparison to measures routinely used in economic evaluation, such as the EQ-5D-3 L. This broader assessment may allow measurement of the full effects of an intervention or treatment. Previous research has indicated that the ICECAP-O (for older people) and EQ-5D-3 L measure provide complementary information. This paper aims to determine similar information for the ICECAP-A (for the entire adult population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 25 publications
11
52
0
Order By: Relevance
“…Firstly, ordinary least squares (OLS) regression methods were used to test whether type of health condition (reporting the presence of one of seven primary health conditions compared to being healthy) had a significant association with capability scores, controlling for age, gender and educational level. Although previous research has employed exploratory factor analysis to validate ICECAP measures compared to other health measures (Davis et al 2013;Keeley et al 2016;Engel et al 2017), our research question required a method to compare the performance of two versions of ICECAP simultaneously. Previous research has demonstrated that OLS models perform well in health-related quality of life outcome studies (Al-Janabi et al 2017), and studies with capability wellbeing measures (Mitchell et al 2013;Mitchell et al 2017b;Franklin et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, ordinary least squares (OLS) regression methods were used to test whether type of health condition (reporting the presence of one of seven primary health conditions compared to being healthy) had a significant association with capability scores, controlling for age, gender and educational level. Although previous research has employed exploratory factor analysis to validate ICECAP measures compared to other health measures (Davis et al 2013;Keeley et al 2016;Engel et al 2017), our research question required a method to compare the performance of two versions of ICECAP simultaneously. Previous research has demonstrated that OLS models perform well in health-related quality of life outcome studies (Al-Janabi et al 2017), and studies with capability wellbeing measures (Mitchell et al 2013;Mitchell et al 2017b;Franklin et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, capability instruments could also be perceived as enhanced rather than complementary to the narrow interpretation of well-being/quality of life when focusing only on HRQoL. Most studies [25][26][27] found that the ICECAP and EQ-5D instruments provide complementary information, and a mapping is not recommended between them. Engel et al [24] found that the ICECAP-A provides evidence above that gathered from most commonly used preference-based HRQoL instruments.…”
Section: Validation Of Capability Instrumentsmentioning
confidence: 99%
“…Perhaps this should not be surprising as the ICECAP measures potentially offer a broader assessment of QoL and well-being than measures routinely used in economic evaluation such as the EQ-5D-3L. 108 This broader assessment may allow measurement of the full effects of an intervention or treatment. Previous research has indicated that the ICECAP-O and EQ-5D-3L measures provide complementary information and are not substitutes for each other.…”
Section: Discussionmentioning
confidence: 99%